2016
DOI: 10.1177/1098612x15605535
|View full text |Cite
|
Sign up to set email alerts
|

Apparent nutrient digestibility of two raw diets in domestic kittens

Abstract: Higher dry matter, organic matter and protein digestibility was seen in two commercial raw diets compared with a heat-processed diet. Digestibility differences could have been due to variance in dietary protein, fat and carbohydrate concentrations between the diets, variance in dietary ingredients or quality, alterations in protein structure secondary to heat processing, as well as alterations in gastrointestinal flora. Future research examining digestibility in diets with the same macronutrient proportions an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 15 publications
(26 reference statements)
2
13
0
Order By: Relevance
“…reported apparent total tract digestibilities in a super-premium, extruded diet of 78.2, 83.9, 81.6, 91.3, and 84.7% for DM, OM, CP, fat, and energy, respectively. Hamper et al, (2015) reported slightly higher values in kittens fed a processed canned diet (83.8, 88.4, 88.9, 94.2, and 90.2% for DM, OM, CP, fat, and energy, respectively). Although high for all treatments, digestibility of fat was lower in dogs fed the Beef 2 diet (94.9%) compared with other treatments that averaged 97.8%.…”
Section: Feed Intake Fecal Outputs and Fecal Scoresmentioning
confidence: 88%
See 4 more Smart Citations
“…reported apparent total tract digestibilities in a super-premium, extruded diet of 78.2, 83.9, 81.6, 91.3, and 84.7% for DM, OM, CP, fat, and energy, respectively. Hamper et al, (2015) reported slightly higher values in kittens fed a processed canned diet (83.8, 88.4, 88.9, 94.2, and 90.2% for DM, OM, CP, fat, and energy, respectively). Although high for all treatments, digestibility of fat was lower in dogs fed the Beef 2 diet (94.9%) compared with other treatments that averaged 97.8%.…”
Section: Feed Intake Fecal Outputs and Fecal Scoresmentioning
confidence: 88%
“…A major potential benefit of feeding RMBDs to pets is eliminating the subsequent effects of intensive processing with extrusion or canning. Several studies have demonstrated RMBDs have greater macronutrient digestibility compared to extruded or canned diets Hendricks et al, 1999;Kerr et al, 2013;Hamper et al, 2015). Crude protein digestibility was 9.0% greater (P<0.05) in…”
Section: Advantages Of Rmbdsmentioning
confidence: 99%
See 3 more Smart Citations